1995
DOI: 10.1139/v95-013
|View full text |Cite
|
Sign up to set email alerts
|

On the purported axial preference in 2-methylthio and 2-methoxycyclohex-anones: steric effects versus orbital interactions

Abstract: Abstract:The value for the equilibrium constant representing the ratio of equatorial to axial conformers for 2-methylthio-and 2-methoxycyclohexanone has been measured in five solvents using 500 MHz 'H nuclear magnetic resonance. In cyclohexane solvent, the methylthio group is found to have a large axial preference while that for the methoxy is negligible. For both compounds the equilibrium shows a strong solvent dependence.Comparison of these results with those known for the halo derivatives shows the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Analysis of the 1 H NMR data in CDCl 3 for a diastereomeric mixture of 2-phenylsulfinylcyclohexanone (A + B) had indicated the presence of two H-2 resonances at 3.31 and 3.55 ppm (12) 4 . Comparison of line widths with those of anancomeric, conformationally biased derivatives indicated that the isomer A, whose chemical shift was 3.31 ppm, existed as a 3:2 mixture of axial:equatorial conformers, whereas B, whose chemical shift was 3.55 ppm, existed as a 2:1 mixture of equatorial:axial conformers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the 1 H NMR data in CDCl 3 for a diastereomeric mixture of 2-phenylsulfinylcyclohexanone (A + B) had indicated the presence of two H-2 resonances at 3.31 and 3.55 ppm (12) 4 . Comparison of line widths with those of anancomeric, conformationally biased derivatives indicated that the isomer A, whose chemical shift was 3.31 ppm, existed as a 3:2 mixture of axial:equatorial conformers, whereas B, whose chemical shift was 3.55 ppm, existed as a 2:1 mixture of equatorial:axial conformers.…”
Section: Resultsmentioning
confidence: 99%
“…It had been suggested that the increased axial preference for the heavier chalcogen substituents was due to the increased nonbonded repulsion with the carbonyl group in the equatorial conformer (3,4). However, the possibility of the role of σ C-X → π C O = * and n X → π C O = * stabilizing orbital interactions as contributors to the conformational preferences was also recognized ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This is good evidence that all these compounds adopt one preferred conformation and that these values do not correspond to mean values reflecting equilibria between two, or possibly even more, conformations. 15 Finally, it is interesting to note, that the (formal) OCH 3 -addition to lactones 1 and 2 occurs regiospecifically at C(5) whereas for ketone 9 20% of the O,S-acetal 11 is also formed. A possible reason for this could be a different degree of twisting around the C-C double bond in the excited unsaturated molecules, the bulky substituents on C(2) totally hindering the approach of methanol to C(6) in the unsaturated lactones, but only partially in the unsaturated ketone, respectively.…”
Section: Methodsmentioning
confidence: 98%
“…In the vapor phase and in non-polar solvents, three factors may contribute to a preference for the axial conformation. 27 A steric effect between the lone pairs of the oxygen and the asubstituent and a repulsive dipole-dipole interaction (both in the equatorial conformer) and an interaction between the n Br and p* CO orbitals. In polar solvents, the second factor will be decreased and the equatorial conformer becomes more stable and has the larger population.…”
Section: Conformational Preferencesmentioning
confidence: 99%